Adolescents in provisional reception: investigative analysis about the vulnerability to HIV - Lilian Joane Cavalcanti; Richardson Augusto Rosendo Da Silva; Ana Raquel Cortês Nelson; Jose Rebberty Rodrigo Holanda; Nanete Caroline da Costa Prado; Mayara Mirna do Nascimento Costa (Universidade Federal do Estado do Rio de Janeiro, 2015)
ABSTRACT Objective: To Investigate the vulnerability of teenagers in foster provisional HIV. Method: A descriptive study and exploratory qualitative way. Study participants were the street teenagers, attendees of the Casa de Passagem III, in Natal City, of state Rio Grande do Norte. With the technique of Focus Group (FG),  Results: The topics were addressed in relation to knowledge about HIV/AIDS; self-protectio and responsibility on sexuality; sexual behaviors and values; and the institution's contribution in protecting against HIV/AIDS. Conclusion: The teenagers perceptions about HIV vulnerabilities, reflect others social problems, demonstrating the want to intervene based on multiple ways, principally, highlighting the social needs of these teenagers. Descriptors: Vulnerability, Teens, HIV.   RESUMO Objetivo: Analisar as percepções dos adolescentes em acolhimento provisório quanto a sua a vulnerabilidade ao HIV. Métodos: Estudo descritivo e exploratório de natureza qualitativa. Realizado com adolescentes institucionalizados na Casa de Passagem III localizada em Natal, no Estado do Rio Grande do Norte. Mediante a técnica do Grupo Focal (GF) Resultados: Foram abordados elementos em relação aos conhecimentos sobre HIV/Aids; auto-proteção e responsabilização na esfera sexual; comportamentos e valores; e contribuição da instituição na prevenção ao HIV/Aids. Conclusão: As percepções dos adolescentes em relação à vulnerabilidade ao HIV refletem outros problemas sociais, evidenciando a necessidade da intervenção baseada em múltipla direção, principalmente, em resposta a necessidades sociais desses adolescentes. Descritores: Vulnerabilidade, Adolescentes, HIV.   RESUMEN Objetivo: Analizar las percepciones de los adolescentes en acogida provisionales como su vulnerabilidad al VIH. Métodos: Un carácter descriptivo, exploratorio y cualitativo. En el estudio, los adolescentes con una historia de la vida en la calle, institucionalizado en la Casa de Passagem III ubicado en Natal, Rio Grande do Norte. A través de la técnica del Grupo Focal (GF). Resultados: Tras examinar los elementos en relación con los conocimientos sobre el VIH/SIDA, la autoprotección y la responsabilidad en la esfera sexual, comportamientos y valores, y la contribución de la institución en la prevención del VIH/SIDA. Conclusión: Las percepciones de los adolescentes en relación con la vulnerabilidad al VIH reflejan otros problemas sociales, destacando la necesidad de una intervención basada en la dirección múltiple, sobre todo en respuesta a las necesidades sociales de los adolescentes. Descriptores: Vulnerabilidad, Adolescentes, VIH.